MITOS KEBEBASAN WANITA DALAM IKLAN (ANALISIS SEMIOTIKA ROLAND BARTHES PADA IKLAN 3 / TRI VERSI KEBEBASAN WANITA DI TELEVISI ) - Utomo, Ichsan Widi (Universitas Bina Sarana Informatika, 2017)
Women in society are still seen as being in a position that is considered as the oppressed and weak than men , because women 's oppression often feel constrained in the right or freedom . Related to this ad female provider 3 lifting of freedom that occurs in the community as the content of the advertising message . The purpose of this study was to uncover the myth of women's liberation is behind the ad 3 versions Women Freedom , by identifying the signs contained in the advertisement is the subjective meaning of the ad . The method used is a qualitative method that is interpretative , namely by direct observation of the overall ad 3 versions of the freedom of women on television . This study uses analysis Semiotics of Roland Barthes , in order to know the myth of women's liberation in 3 ads on television where meaning-making process by semiotics .The results of this study is that there is a myth that unfettered freedom , the use of the property and a use of a model bird woman in everyday life - day . Modern woman who still hit the rules of the system are tied culture , the culture that gave birth to the stereotype that women are free to express and do anything , but still there are limitations . In addition there is the myth of parole shows that women are not free in principle , the ad is shown that the role of women experiencing setbacks in their social system because of cultural rules that they follow . Â Keywords: Women, Freedom, Advertising, Semiotics